Uso da homeopatia no tratamento da depressão: uma revisão narrativa - Guimarães, Nathália Kembelly Nascimento (Brasil, 2021)
Homeopathy is a medical and pharmaceutical specialty that seeks to treat the patient with minimal amounts of medicine with the objective of stimulating the system itself so that the patient can recover. Depression is a disease that affects millions of people around the world and in Brazil the number of people affected by this disease is growing. The treatment of depression is done through the use of antidepressants and psychotherapy, but these medications have many reports of important adverse effects. The present work is a narrative literature review that sought to inform what the specialized health literature says about the Use of homeopathy in the treatment of depression. Homeopathy is a part of medicine that has as its main objective the cure not only in the physical sphere of the patient but also in the emotional and mental level. A survey of articles related to the topic was carried out and the databases and journals Scientific Electronic Libray Online – SciELO, CAPES journal portal, as well as research through dissertations and monographs using Google Scholar, were used as a basis for the research. Following the inclusion and exclusion criteria, 05 studies were selected for analysis, of which 80% were related to improvement in the quality of life of users and 20% discussed access and information to homeopathic treatment. Homeopathic treatment benefits the user as it does not have adverse effects, it is easily accessible and is present in the SUS (Unified Health System).